PENINGKATAN HASIL BELAJAR KOGNITIF MAHASISWA MELALUI MODEL PEMBELAJARAN GROUP DISCOVERY LEARNING (GDL) PADA MATAKULIAH PENGETAHUAN LABORATORIUM DI IKIP BUDI UTOMO MALANG - Prasetyana, Septina Dwi (Program Studi Pendidikan Biologi, IKIP Budi Utomo Malang, 2017)
The paradigm of national education develops along with the demand of human resource improvement through the learning characteristic which centered on the human. The observation result shows that using the conventional method and giving the assignment were still implemented in the learning activity. In this way, the students became less active during the lesson, and got low outcomes on the subject matter of laboratory knowledge. Based on this problem, the learning activity can use an alternative learning model. One of them is Group Discovery Learning (GDL). The research conducted Classroom Action Research (CAR) which used the descriptive approach. This research was conducted in two cycles. Each cycle consisted of planning, implementing, observing, and reflecting. The subject of the research was 43 university students. The conclusion of the research shows that the use of GDL model improves the students’ learning outcomes.